2010
DOI: 10.2355/tetsutohagane.96.272
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Reactive and High Strength Coke by the Addition of Ca-ion Exchanged Brown Coal

Abstract: Synopsis :In order to obtain highly reactive cokes, a Ca-ion exchanged brown coal (Loy-Yang coal) was added to a caking coal (Goonyella coal) with different blending ratios and cokes were then prepared from these blended coal samples. With the addition of Ca-loaded coals, the CO 2 -gasification reactivity of the resulting cokes was significantly increased. Their initial reactivity was particularly enhanced, at a maximum, being thirty times as high as the reactivity of a coke prepared from a single Goonyella co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As the reaction goes on, the coke around the additive is consumed in large quantities, leading to coalescence of coke. A pore structure with additives at the center is formed [35]. The pore structure has little effect on the specific surface area of coke due to its large size; in the part of coke without additive distribution, the reaction is uniform because of no additive catalysis, and the surface of coke is evenly eroded by CO 2 to form micropores, which increases the specific surface area of coke [36].…”
Section: Relationship Between Coke Reactivity and Specific Surface Areamentioning
confidence: 99%
“…As the reaction goes on, the coke around the additive is consumed in large quantities, leading to coalescence of coke. A pore structure with additives at the center is formed [35]. The pore structure has little effect on the specific surface area of coke due to its large size; in the part of coke without additive distribution, the reaction is uniform because of no additive catalysis, and the surface of coke is evenly eroded by CO 2 to form micropores, which increases the specific surface area of coke [36].…”
Section: Relationship Between Coke Reactivity and Specific Surface Areamentioning
confidence: 99%
“…On the other hand, Nomura et al demonstrated the advantage of high-reactivity coke over conventional cokes for the use in a blast furnace . The reactive coke decreased the thermal reserve zone temperature, improving blast furnace reaction efficiency. In Japan, the CO 2 Ultimate Reduction in Steelmaking Process by Innovative Technology for Cool Earth 50 (COURSE50) national project necessitates development of a high-reactivity coke because of the operation of the blast furnace under an atmosphere rich in hydrogen, which inhibits the gasification of coke.…”
Section: Introductionmentioning
confidence: 99%